PENGUATAN KONSEP MITIGASI BENCANA GEMPA BUMI DAN TSUNAMI DI SDN 07 KECAMATAN TELUK SEGARA KOTA BENGKULU - Zulfia Memi Mayasari; Nur Afandi; Siska Yosmar; Lidya Savitri; Meca Nerdika; Fajri Ramadan; Nova Asri Ramdhani (LP2M Universitas Hasanuddin, 2024)
SDN 07 Bengkulu City is an elementary school located in Teluk Segara District which is quite close to the beach. Because of this position factor, this school is very vulnerable to risks of earthquake and tsunami disasters. Therefore, this school must have preparedness in face of disasters that can occur at any time. In fact, disaster mitigation education in this school is very minimal. In addition, this school does not yet have the necessary evacuation routes when a disaster strikes. The purpose of this community service is to create an evacuation route in SDN 07 Bengkulu City and increase the awareness of the residents of SDN 07 schools against earthquake and tsunami disasters. This activity is carried out through several stages of implementation, namely: Setting targets and targets to be achieved, compiling materials related to disaster mitigation which are packaged in the pocket book, installing directions for evacuation routes in the school environment, making maps of evacuation routes in schools, and carrying out socialization and simulation of disaster mitigation. The results obtained from this activity are a pocket book on earthquake and tsunami disaster mitigation, the installation of directions for evacuation routes in the school environment, availability an evacuation route map at SDN 07 Bengkulu City and increasing awareness, understanding and knowledge of school residents about the concept of disaster mitigation. — SDN 07 Kota Bengkulu merupakan sekolah dasar yang terletak di Kecamatan Teluk Segera yang jaraknya cukup dekat dengan pantai. Karena faktor posisi inilah maka sekolah ini sangat rentan terhadap resiko bencana gempa bumi dan tsunami. Oleh karena itu sekolah ini harus memiliki kesiapsiagaan dalam menghadapi bencana yang dapat terjadi kapan saja. Faktanya, pendidikan mitigasi bencana di sekolah ini sangat minim. Selain itu, sekolah ini belum memiliki jalur evakuasi yang diperlukan saat bencana datang. Tujuan dari kegiatan pengabdian ini adalah membuat jalur evakuasi di lingkungan SDN 07 Kota Bengkulu dan meningkatkan kewaspadaan warga SDN 07 terhadap bencana gempa bumi dan tsunami. Kegiatan ini dilakukan melalui beberapa tahap pelaksanaan yaitu: Menetapkan target dan sasaran yang akan dicapai, menyusun materi yang berkaitan dengan mitigasi bencana yang dikemas dalam bentuk buku saku, memasang petunjuk arah jalur evakuasi di lingkungan sekolah, membuat peta jalur evakuasi di sekolah, serta melaksanakan sosialisasi dan simulasi mitigasi bencana. Hasil yang diperoleh dari kegiatan ini adalah buku saku mengenai mitigasi bencana gempa dan tsunami, terpasangnya petunjuk arah jalur evakuasi di lingkungan sekolah, tersedianya peta jalur evakuasi di SDN 07 Kota Bengkulu dan meningkatnya kesadaran, pemahaman dan pengetahuan warga sekolah tentang konsep mitigasi bencana.